THE IMPACT OF INTERNATIONAL OIL PRICE ON NIGERIA’S EXPORT REVENUE - MOSHOOD, KOLAWOLE ALABI; FIYINFOLUWA , EMMANUEL OJEDIRAN (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
As one of Africa’s leading oil producers, Nigeria is heavily reliant on oil exports and this accounts for over 90% of its total export revenue. This study examined the effect of international oil price changes on Nigeria’s export revenue and the direction of granger causality between 1985 and 2022. To achieve these objectives, a Vector Autoregressive model was used to capture the dynamic relationship. Independent variables in the model include Gross Domestic Product, inflation rate and exchange rate. Granger causality test was also carried out to detect the direction of causality. Findings showed a positive relationship between changes in international oil price and changes in Nigeria’s export revenue in the short run. A one unit increase in oil price leads to a 2.17 unit increase in export revenue. However, the long term results showed a negative relationship between oil price and export revenue. Findings also showed that there is a unidirectional causality running from oil price to export revenue. This study underscored the urgent need for economic diversification strategies to mitigate vulnerabilities associated with over-reliance on oil, thereby fostering a more resilient economic framework.